2011
DOI: 10.1080/17470218.2011.575947
|View full text |Cite
|
Sign up to set email alerts
|

Rapid communication: Semantic size does not matter: “Bigger” words are not recognized faster

Abstract: Sereno, O’Donnell, and Sereno (2009) reported that words are recognised faster in a lexical decision task when their referents are physically large rather than small, suggesting that “semantic size” might be an important variable that should be considered in visual word recognition research and modelling. We sought to replicate their size effect, but failed to find a significant latency advantage in lexical decision for “big” words (cf. “small” words), even though we used the same word stimuli as Sereno et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 18 publications
4
26
2
Order By: Relevance
“…For example, imageability effects in monosyllabic word-naming performance were no longer significant once AoA was controlled for (Cortese & Khanna, 2007). Likewise, the semantic size variable introduced by Sereno, O'Donnell, and Sereno (2009) did not account for variance in lexical-decision performance when correlated variables were included in the analysis with 324 words (Kang, Yap, Tse, & Kurby, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…For example, imageability effects in monosyllabic word-naming performance were no longer significant once AoA was controlled for (Cortese & Khanna, 2007). Likewise, the semantic size variable introduced by Sereno, O'Donnell, and Sereno (2009) did not account for variance in lexical-decision performance when correlated variables were included in the analysis with 324 words (Kang, Yap, Tse, & Kurby, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Both facilitation (Zwaan et al, 2002) and interference (Richardson, Spivey, Barsalou, & McRae, 2003) have also been reported for orientation. Finally, Kang, Yap, Tse, and Kurby (2011) failed to replicate an effect of object size reported by Sereno, O’Donnell, and Sereno (2009).…”
mentioning
confidence: 78%
“…For example, by performing analyses on normative data of a much larger word pool in Balota et al's (2007) English Lexicon Project, Kang, Yap, Tse, and Kurby (2011) found that the semantic size effect (i.e., faster lexical decision RTs to words when their referents are physically large, e.g., elephant, than when they are small, e.g., needle) might not generalize beyond the original stimulus set used in earlier studies (see also Juhasz, Yap, Dicke, Taylor, & Gullick, 2011, for New, Ferrand, Pallier, and Brysbaert (2006) found a U-shaped effect of word length on English lexical decision (facilitative for words of 3-5 letters, null for words of 6-8 letters, and inhibitory for words of 9-13 letters), contradicting the view that longer words always take more time to process. By conducting item-level multiple regression analyses on lexical decision performance based on a larger pool of words, the linear and/or nonlinear of effect of targeted variables would be captured more easily, which could not be observed in factorialdesign experiments where variables are dichotomized.…”
Section: Discussionmentioning
confidence: 99%